2015
DOI: 10.1186/s13287-015-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting poor peripheral blood stem cell collection in patients with multiple myeloma receiving pre-transplant induction therapy with novel agents and mobilized with cyclophosphamide plus granulocyte-colony stimulating factor: results from a Gruppo Italiano Malattie EMatologiche dell’Adulto Multiple Myeloma Working Party study

Abstract: Introduction: A still not well defined proportion of patients with multiple myeloma (MM) and eligible for autologous stem cell transplantation (AuSCT) fails to mobilize CD34+ peripheral blood stem cells (PBSC) at all or to collect an adequate number for a safe procedure or sufficient for multiple transplants. These so-called "poor-mobilizers" are difficult to be predicted, due to marked difference across previous heterogeneous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 31 publications
5
27
1
3
Order By: Relevance
“…Our definition of poor mobilizers was a practical one but slightly different from other definitions used in previous publications. Furthermore, in our program, we recommend non‐lenalidomide containing induction therapy, mainly cyclophosphamide/bortezomib/dexamethasone, which may explain the lower number of patients who received lenalidomide in their first induction regimen and possibly the relatively lower frequency of poor mobilizers (10.4%), whereas many other studies reported > 15% incidence . Another possible limitation is the relatively small number of patients treated with CXCR4 antagonist plerixafor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our definition of poor mobilizers was a practical one but slightly different from other definitions used in previous publications. Furthermore, in our program, we recommend non‐lenalidomide containing induction therapy, mainly cyclophosphamide/bortezomib/dexamethasone, which may explain the lower number of patients who received lenalidomide in their first induction regimen and possibly the relatively lower frequency of poor mobilizers (10.4%), whereas many other studies reported > 15% incidence . Another possible limitation is the relatively small number of patients treated with CXCR4 antagonist plerixafor.…”
Section: Discussionmentioning
confidence: 99%
“…In MM, multiple studies reported lenalidomide use to be another risk factor for poor mobilization . Most studies use different definitions for poor mobilization in MM patients, mainly due to the practice of collecting upfront adequate numbers of stem cells for two transplants …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the right timing for administration of plerixafor is unknown: preventively on the day before the start of collection or “on demand” (rescue) in cases of poor apheresis results. Thus, identifying candidate patients who are “poor mobilizers” is important, and numerous types of biological and clinical data have been proposed to be useful for identifying these patients, but there is no consensus on the use of these indicators . In addition, there are authors who have tried other mobilizing agents, such as bortezomib, in combination with the above mentioned agents.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with poor mobilization were age and hematological toxicity during prior induction. [12] Novel strategies for optimizing stem cell collection includes the addition of the alpha chemokine receptor CXCR4 antagonist plerixafor in selected patients. Lemoli et al reported a prospective study on the use of plerixafor in 83 MM patients who were poor mobilizers.…”
Section: Stem Cell Collectionmentioning
confidence: 99%